Hearing levels in patients with alzheimer’s dementia - Akyiğit, Abdulvahap; Subaşi, Burak; Sakallioğlu, ÖNer; Polat, Cahit; Düzer, Sertaç; Keleş, Erol; Özer, Necdet (Geriatrics Society, 2014)
Introduction: It has been assumed that hearing loss may be related to dementia and prevents social interaction by decreasing stimulus input. The current study investigated the relationship between hearing loss and dementia by comparing Alzheimer’s dementia patients to non-dementia patients.; Materials and Methods: Between January 2011 and January 2013, 124 Alzheimer’s dementia patients diagnosed by the mini-mental state examination and 224 non-dementia controls who applied to the Psychiatry Clinic of Elazığ Training and Research Hospital were included in the study. Hearing levels of the Alzheimer’s dementia patients and non-dementia controls were obtained using a pure tone audiometry test.; Results: The pure tone average was determined to be 50.96±12.25 dB and 50.49±12.15 dB, consecutively, in the right and left ears of Alzheimer’s dementia patients. In the Alzheimer’s dementia group of patients, researchers detected 6 (4.8%) patients with normal hearing, 23 (18.5%) patients with mild hearing loss, 57 (46%) patients with moderate hearing loss, and 38 (30.6%) patients with severe hearing loss. The pure tone average was determined to be 30.66±9.33 dB and 30.62±9.39 dB, consecutively, in the right and left ears of the control patients. In non-dementia controls, the researchers also detected 83 (38.8%) patients with normal hearing, 106 (45.5%) patients with mild hearing loss, 21 (9.8%) patients with moderate hearing loss, and 4 (1.9%) patients with severe hearing loss. The differences in the pure tone average of the right and left ears between Alzheimer’s dementia patients and non-dementia controls were statistically significant (P<0.05). Nine (7.2%) Alzheimer’s dementia patients and 6 (2.8%) controls were already using hearing devices.; Conclusion: The current study revealed that hearing loss was significantly higher in Alzheimer’s dementia patients compared to non-dementia patients; this result indicates a relationship between dementia and hearing loss. Therefore, the researchers believe that hearing aids should be proposed for patients with geriatric hearing loss, with or without dementia, if they have relatively good cognitive functionality. Use of hearing aids could increase their cognitive and daily functioning. © 2014, Geriatrics Society. All rights reserved.
Alzheimer demans tanili hastalarda ifiitme düzeyi
Keywords: Alzheimer dementia; Geriatrics; Hearing loss